Perceptual Transcendence of Objects: “Borderless”Revolution of Qiyun-Atmosphere Aesthetics in Context of Cultural Economy (Global Journal of Human-Social Science, 2023)
Chinese classical aesthetics attributes the occurrence of aesthetics to human heart s response to foreign objects and believes that through this response aesthetic effects such as artistic conception image and Qiyun can be realized The current cultural economy has created a new relationship between mind and object under the background of aesthetic capitalism This relationship between mind and object unties the bondage of objects to human beings expands the aesthetic boundary constantly stimulates the creative potential of social individuals creates aesthetic democracy and breaks the stereotype that economic growth is the only standard of social development However it will also materialize people s feeling structure liberate sensibility excessively and hinder the development of real freedom and democracy in society Integrating Chinese qiyun aesthetics with German atmosphere aesthetics and exploring a new aesthetic way in context of culture and economy will correct this disadvantage to a certain extent Through perceptual transcendence the new aesthetic way reflects the characteristics of daily life mobility non-positioning and strong emotional appeal Therefore the aesthetic revolution triggered by it can be called borderless revolution Such revolution can help to build a human aesthetic community under the background of cultural economy
Keywords: objects; sensibility; cultural economy; qiyun- atmosphere aesthetics; borderless